2020
DOI: 10.1016/j.hpb.2020.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Prospective double-blinded randomized controlled trial of Microwave versus RadioFrequency Ablation for hepatocellular carcinoma (McRFA trial)

Abstract: Background: Microwave (MWA) and radiofrequency ablation are the commonly used local ablation for hepatocellular carcinoma (HCC). Studies comparing both techniques are scarce. The aim of this study was to compare the efficacy of MWA versus RFA as a treatment for HCC.Methods: Patients with HCC who were suitable for local ablation were randomized into MWA or RFA. All patients were followed up regularly with contrast-enhanced computed tomography (CT) performed at 1, 3, 6 and 12 months after ablation. Both patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 29 publications
1
54
0
2
Order By: Relevance
“…Two studies assessed ablation time. [ 26 , 29 ] The median ablation time was shorter in the MWA group (12 minutes) compared with the RFA group (29 minutes) (WMD = –15.674, 95% CI = –17.187 to –14.161, I 2 = 6.5%, P < .001).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Two studies assessed ablation time. [ 26 , 29 ] The median ablation time was shorter in the MWA group (12 minutes) compared with the RFA group (29 minutes) (WMD = –15.674, 95% CI = –17.187 to –14.161, I 2 = 6.5%, P < .001).…”
Section: Resultsmentioning
confidence: 98%
“…Theoretically, multipolar needles could provide a larger ablation range than monopolar needles and result in a shorter ablation time. [ 26 ] However, due to the small number of samples that compare the efficacy of multipolar needles among studies, further investigations are still needed to compare different ablations using different needles. In our meta-analysis, we found that the proportion of patients under local anesthesia was greater in the WMA group compared with the RFA group.…”
Section: Discussionmentioning
confidence: 99%
“…Many treatment modalities are available for the local ablation of hepatocellular carcinoma with generally similar outcomes. [82][83][84][85][86] Radiofrequency ablation and microwave ablation are the most commonly used ablation treatments. A recent, multicenter, single blinded, phase II randomized controlled trial enrolled 76 patients for radiofrequency ablation and 76 patients for microwave ablation; patients each had a maximum of three hepatocellular carcinoma lesions of up to 4 cm each.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…84 However, another randomized trial of 93 patients with hepatocellular carcinoma receiving microwave ablation or radiofrequency ablation showed no difference in treatment related morbidity, overall survival, or disease free survival, although procedure time was shorter with microwave ablation. 85 Percutaneous ethanol ablation induces tumor cell death via intracellular dehydration and activation of coagulation cascades. Local tumor control is not as effective as other local ablation modalities.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…However, it must be emphasized that the majority of the initial studies were retrospective in nature and on small cohorts. Until now, only 5 randomized control (RCT) studies were published showing no difference between MWA and RFA for small HCC [46][47][48][49][50] (Table II). Consequently, two metanalysis found no major differences between the two ablation techniques [51][52].…”
Section: Mwa In Hepatocellular Carcinomamentioning
confidence: 99%